Study on the Bearing Characteristics and the Influence of Pile Characteristics of Rotary Drilling Screw-Shaped Pile - Sifeng Zhang; Yang Xing; Gongfeng Xin; Guodong Chen; Guanxu Long; Pengfei Ma; Jianyong Han (Buildings)
Due to the advantages of high bearing capacity, small settlement of pile body, and high material utilization rate, rotary drilling thread special-shaped pile (RDTSSP) has been applied in pile foundation engineering at home and abroad. Through the field static load test, the bearing characteristics of the single pile of the rotary drilling screw pile are tested and analyzed. Based on the field-measured data, the stress characteristics of the rotary drilling screw pile are analyzed by FLAC3D6.0 finite difference software, and the pile characteristics affecting the vertical bearing capacity of the rotary drilling screw-shaped pile are studied. The impact of various pile factors, including length, diameter, and the ratio of pile body to screw modulus, as well as the presence of an enlarged bottom, the elastic modulus of the pile, and the ratio of the pile body to soil elastic modulus, on the load-bearing capacity of rotary drilling thread special-shaped pile (RDTSSP) is examined. The results show that with the increase in pile length, the bearing capacity of the screw-shaped pile increases gradually, but when it increases to a certain value, the increased bearing capacity per unit volume decreases gradually. The increase in pile diameter will lead to a decrease in bearing capacity per unit volume, so the smaller pile diameter should be selected in the design to make full use of the material properties. The bottom expansion has little effect on the bearing capacity, but with the increase in the inner diameter of the bottom expansion, the bearing capacity increases gradually, while the bearing capacity per unit volume decreases and the material utilization rate decreases. Enhancing the modulus of a pile modestly boosts its load-bearing capacity, whereas augmenting the elastic modulus ratio between the pile and the surrounding soil substantially amplifies this capacity. The innovation of this study is to propose a new type of rotary drilling thread-shaped pile, which has significant economic and social benefits in engineering applications.